Papillon lefevre syndrome- An imperative role of periodontist - Santha Kumari, Prathypaty; Satheesh Kumar, Guvvala; Santhi priya, Potharaju; Durga Bai, Yendluri; dathar, Sahithi (International Journal of Dental Research, 2016)
Papillon Lefevre syndrome (PLS) is a rarely encountered disorder that shows autosomal recessive inheritance. Clinically, it exhibits hyperkeratotic plaques on palmar plantar surfaces, severe periodontal loss and precocious shedding of primary as well as permanent dentition. The reason for this exceptional clinical presentation is vague and speculative. We are reporting one such case of a 23year old female patient.